2013
DOI: 10.1186/1477-3155-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Polyamidoamine dendrimer impairs mitochondrial oxidation in brain tissue

Abstract: BackgroundThe potential nanocarrier polyamidoamine (PAMAM) generation 5 (G5-NH2) dendrimer has been shown to evoke lasting neuronal depolarization and cell death in a concentration-dependent manner. In this study we explored the early progression of G5-NH2 action in brain tissue on neuronal and astroglial cells.ResultsIn order to describe early mechanisms of G5-NH2 dendrimer action in brain tissue we assessed G5-NH2 trafficking, free intracellular Ca2+ and mitochondrial membrane potential (ΨMITO) changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…19 An increasing number of studies in diverse cell lines have shown that exposure to cationic dendrimers results in cell membrane permeability, cellular lysis, and cytotoxicity. 9,[20][21][22][23] Recent studies in mice and zebrafish (Danio rerio) have also shown polyamidoamine (PAMAM) dendrimers with amine terminated groups affected blood-clot formation when administered intravenously, while neutral and anionic dendrimers of the same generation demonstrated no observable vascular complications. 24,25 The authors suggest that these effects are driven by the high affinity amine for platelets or vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 An increasing number of studies in diverse cell lines have shown that exposure to cationic dendrimers results in cell membrane permeability, cellular lysis, and cytotoxicity. 9,[20][21][22][23] Recent studies in mice and zebrafish (Danio rerio) have also shown polyamidoamine (PAMAM) dendrimers with amine terminated groups affected blood-clot formation when administered intravenously, while neutral and anionic dendrimers of the same generation demonstrated no observable vascular complications. 24,25 The authors suggest that these effects are driven by the high affinity amine for platelets or vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The low polydispersity index and the ability to precisely control their surface chemistry make dendrimers useful for medical imaging, enhancing the solubility and/or bioavailability of drugs, brain-target drug therapy, and specific targeting mechanism for anti-cancer therapeutics and gene therapy. [8][9][10] The stability, precise size, and defined chemistry of dendrimers also make them ideal for the development of structure-property relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from silica NPs , data on the perturbations of calcium signaling mechanisms induced by NPs are still scarce (see e.g. Huang et al, 2010;Koeneman et al, 2010) and this is particularly true for neuronal cells (Guo et al, 2013;Haase et al, 2012;Nyitrai et al, 2013;Tang et al, 2008aTang et al, , 2008b, as recently reviewed (Lovisolo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PAMAM dendrimers exhibit neuronal toxicity. For example, unmodified PAMAM G5-NH 2 induces mitochondrial membrane potential depolarization in neurons and astroglial cells [55] and activates autophagy [56]. PAMAM dendrimers also increase reactive oxygen species and DNA damage in a generation-dependent manner [57].…”
Section: Dendrimersmentioning
confidence: 99%